2008
DOI: 10.4049/jimmunol.180.12.7818
|View full text |Cite
|
Sign up to set email alerts
|

The Innate NK Cells, Allograft Rejection, and a Key Role for IL-15

Abstract: Transplant rejection is mediated primarily by adaptive immune cells such as T cells and B cells. The T and B cells are also responsible for the specificity and memory of the rejection response. However, destruction of allografts involves many other cell types including cells in the innate immune system. As the innate immune cells do not express germline-encoded cell surface receptors that directly recognize foreign Ags, these cells are thought to be recruited by T cells to participate in the rejection response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
82
0
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(92 citation statements)
references
References 35 publications
(40 reference statements)
5
82
0
4
Order By: Relevance
“…In particular, because IL-15 plays a key role in the development, survival, homeostasis, proliferation, and maturation of NK cells and cytotoxic T cells (Tc cells) (30)(31)(32)(33)(34)(35), it has therapeutic promise for anticancer immunotherapy (36). The systemic use of IL-15 was shown to prolong the survival of mice with metastatic CRC and other tumors through activation of Tc cells and NK cells (37)(38)(39)(40)(41).…”
mentioning
confidence: 99%
“…In particular, because IL-15 plays a key role in the development, survival, homeostasis, proliferation, and maturation of NK cells and cytotoxic T cells (Tc cells) (30)(31)(32)(33)(34)(35), it has therapeutic promise for anticancer immunotherapy (36). The systemic use of IL-15 was shown to prolong the survival of mice with metastatic CRC and other tumors through activation of Tc cells and NK cells (37)(38)(39)(40)(41).…”
mentioning
confidence: 99%
“…В модели, включающей родительский по отношению к F1-потомку трансплантат сердца, CAV развивалась в трансплантатах сердца по НК и IFN-g зависимым механизмам [164], подчёркивая тем самым роль НК в патогенезе хронического отторжения трансплантата. В дополнение к содействию в отторжении, опосредованном Т-клетками, НК прямо ответственны за отторжение трансплантата в некоторых животных моделях [5,165,166]. Парадоксально, что, несмотря на вышеизложенные данные, указывающие на роль НК в отторжении, в некоторых животных моделях они также принимают Долгих участие в иммунной регуляции и необходимы для установления толерантности аллотрансплантата.…”
Section: натуральные киллеры (нк)(Nk)unclassified
“…In the conventional theory, NK cells participate in transplantation rejection as effector cells, which can mediate cytolytic effects against allogeneic and xenogeneic cells via the antibody-dependent cell-mediated cytotoxicity mechanism (Kumagai-Braesch et al 1998) and produce a variety of proinflammatory cytokines that promote the maturation of APCs and indirectly amplify T cell activation (Kroemer et al 2008a). Kroemer et al (2008b) reported that NK cells could reject skin allografts when stimulated with interleukin (IL)-15 in the absence of adaptive immune cells. However, recent studies have demonstrated that NK cells can kill allogeneic graft-derived APCs and prolong the survival of skin grafts through the inhibition of direct T cell priming or the elimination of activated alloreactive T cells in a perforin-dependent mechanism (Beilke et al 2005;Yu et al 2006).…”
Section: The Characteristics Of Skin Graft Immunologymentioning
confidence: 99%